Fortalecimiento del desempeño de los niños de 1° primaria en la resolución de problemas de estructura aditiva: cambio y combinación (2014)
This research paper seeks to show that learning mathematics requires a systematic process of education considering the cognitive development of the person. Likewise, it should be noted that although the person has innate predispositions, he needs social interaction so that these predispositions can be strengthened. Therefore, according to Vygotsky, when teaching mathematics, it would be grateful that the teacher would be a mediator between the person and the knowledge that hasn’t been reached yet by using scaolding strategies, in which there is evidence of support among both. For this research, a quasi-experimental design was used, which included the participation of 26 students for the control group and 25 for the experimental group in the first elementary level; these studentes carried out a pre and post-test to analyze their initial state for problem solving and their perception towards mathematics. Besides, the impact that the pedagogical intervention had on it. It was possible to determine that the use of mathematical language in communicating symbolic notation systems, the capacity for reasoning and making guesses when solving a problem, strengthened transversely other skills such as reading and writing.